ANALISIS STRATEGI HARGA DAN KUALITAS PRODUKSI TERHADAP KEPUASAN KONSUMEN PADA PERUSAHAAN KUE HJ. ENONG BAKERY DI MARTAPURA - Muhammad Fikri Rahman; Farida Yulianti; Rina - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, This research aims to analyze how the product pricing strategy towards consumer and analyzed the product quality strategy towards consumer satisfaction at Hj. Enong Bakery Company Martapura. This research uses a descriptive quantitative research design. Sampling used in this study was to use the snowball sampling method. Sampling and measurements using the Isaac and Michael formula are samples of Hj. Enong amounted to 32 samples from 35 people in the total population of Hj. Enong Bakery customers and data collection techniques using questionnaires individually. The results of this research indicate the price of the product is in the medium category, which means the price of the product has an impact on customer satisfaction degree. The product price implementation was implemented quite well, from the many responses stating that it agreed to prove that the price given by the Cake Company Hj. Enong Bakery provides satisfaction to consumers, Product quality is in the medium category, which means product prices have an impact on customer satisfaction degree. Product quality is maintained well, it can be proven from the many responses that state that it agrees to the quality of the product, this proves the quality of the products provided by the Cake Company Hj. Enong Bakery provides satisfaction to consumers.